Peelable ultrathin carrier copper foil and preparation process thereof
By forming a composite peeling layer on the metal foil carrier layer and depositing the ultra-thin copper foil layer by double-layer acid copper plating process, the problem of poor bonding force between the carrier copper and ultra-thin copper is solved, and the uniformity and density of the ultra-thin copper foil layer is achieved, avoiding pinholes and adhesion phenomena.
Patent Information
- Application Number
- CN202411786427.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
In the existing ultra-thin copper foil preparation process, the bonding force of the isolation layer between the carrier copper and ultra-thin copper is poor, resulting in uneven deposition of the copper layer, pinholes and adhesion.
Using the double-layer acid copper plating process, the chromium release layer and the alloy release layer are first deposited on the metal foil support layer to form a composite release layer, and then secondary electroplating is performed to deposit the ultra-thin copper foil layer.
The uniformity and density of the ultra-thin copper foil layer are achieved, pinholes and adhesions are avoided, and the complete peeling of the carrier layer is ensured.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of rolled copper foil preparation, and in particular to a peelable ultra-thin carrier copper foil and a preparation process thereof. Background Art
[0002] In recent years, with the popularization of various digital electronic products such as mobile phones and computers, electronic products have gradually filled all aspects of life, so the high integration and lightweight of electronic products are also gradually developing. Ultra-thin copper foil has excellent electrical and thermal conductivity and a thickness of only 1-5μm, so it can effectively improve the working efficiency and performance of electronic components. At the same time, it also has high strength and good corrosion resistance, which can greatly improve the reliability and life of electronic components. The application field of ultra-thin copper foil is very wide, mainly involving semiconductors, electronics, medical, automobiles and many other fields. In the semiconductor field, copper foil, as one of the most basic materials, is widely used in wafer manufacturing, OLED display manufacturing, CMOS image sensor manufacturing, etc. In the electronics field, copper foil is mainly used in the manufacture of PCB boards, capacitors, resistors and other components. At present, the ultra-thin copper foil field is mainly based on imported Mitsui ultra-thin carrier copper foil, so it is imperative to research and develop domestic ultra-thin carrier copper foil.
[0003] Copper foil with a thickness of ≤12μm is usually called ultra-thin copper foil. Its preparation requirements are high and it is easy to wrinkle and tear, so the carrier process came into being. The carrier foil is used as the cathode to electro-deposit the ultra-thin copper foil. When used downstream, it is hot-pressed and cured on the insulating substrate, and then the carrier foil is peeled off to obtain a PCB board loaded with ultra-thin copper. Therefore, the isolation layer between the carrier copper and the ultra-thin copper is very important. The peeling layer is mainly divided into organic and inorganic. The organic peeling layer process is simple, but the poor conductivity leads to uneven thickness of the copper foil layer; the inorganic peeling layer is a metal layer, and the ultra-thin layer can be removed due to the difference in bonding force, but it will cause uneven deposition of the copper layer, pinholes and adhesion.
[0004] At the same time, in order to ensure the integrity and uniformity of the ultra-thin copper foil, the selection of plating solution and the electroplating process of the electroplated copper layer are also very important. There are two main types of electroplating copper plating solutions. Alkaline copper plating has stable plating solution composition, long service life, and a wide range of working temperature and solution concentration. The disadvantage is that its electroplating efficiency is low, and scale and impurities will be generated during the electroplating process, affecting production efficiency. Acid copper plating has good flatness of the coating, simple plating solution composition and low production cost. The application number is CN202410366602.2. The preparation method of the ultra-thin carrier copper foil that is easy to peel and the ultra-thin carrier copper foil, the copper electroplating solution used includes the following components: 100-400g / L of copper sulfate pentahydrate, 20-200g / L of 98% sulfuric acid, 0.01-0.5g / L of sodium chloride, 0.2-1.2g / L of polydisulfide dipropane sulfonate sodium, 0.2-1.5g / L of polyethylene glycol 8000, 0.2-1.5g / L of hydroxyethyl cellulose, and 0-0.5g / L of bone glue. The disadvantage is that the pre-treatment requirements are relatively high, that is, the substrate surface needs to be uniform and free of impurities. Therefore, the plating solution for the ultra-thin copper layer selected in this paper is an acidic plating solution with copper sulfate as the main body. However, due to the high cathode plating efficiency of acid electroplating, the plating speed is too fast, which will cause hydrogen embrittlement, making the coating less dense, resulting in pinholes and coating embrittlement. Therefore, double-layer acid electroplating is used for secondary electroplating. The copper layer is electroplated twice at different current densities to ensure its density and uniformity. Summary of the invention
[0005] In view of the above problems existing in the prior art formula, the present invention performs double-layer acid copper plating on the metal foil carrier layer, so that the metal foil carrier layer can be peeled off normally, and the ultra-thin copper foil layer has no pinholes and adhesion.
[0006] In order to achieve the above technical purpose, the specific preparation process is as follows: Step 1: pre-treat the metal foil carrier layer; the metal foil carrier is a copper foil carrier, and the surface roughness is 0<Rz≤0.7μm Step 2: depositing a composite release layer on the glossy surface of the metal foil carrier; A chromium-containing electroplating solution and an alloy-containing electroplating solution are prepared respectively, and a chromium stripping layer is first deposited on the smooth surface of the pretreated metal foil carrier, and then an alloy stripping layer is deposited, and the two together serve as a composite stripping layer; Step 3: depositing an ultra-thin copper foil layer on the composite peeling layer; The process for depositing the ultra-thin copper foil layer is secondary electroplating of an acid copper plating solution, wherein the acid copper plating solution comprises 70-90 g / L copper sulfate, 140-160 g / L sulfuric acid, 4-6 mg / L polyethylene glycol, and 0.1-0.3 mg / L methyl cellulose, and the temperature of the acid copper plating solution is 25-50°C.
[0007] Furthermore, the acid copper plating solution comprises 80 g / L copper sulfate, 150 g / L sulfuric acid, 5 mg / L polyethylene glycol, and 0.2 mg / L methyl cellulose, and the temperature of the acid copper plating solution is 50°C.
[0008] Furthermore, in the step 3, an acid copper plating solution is prepared and injected into two tanks respectively; Electroplating is performed on the composite peeling layer of the copper foil carrier, and the current density of the first slot is 10-100A / dm 2 , the electrodeposition time is 20-100s; After electroplating in the first tank, the copper foil carrier gradually passes through the squeeze roller, the water washing tank, and the squeeze roller to clean the front acid copper plating solution and enter the second tank for electroplating. The current density of the second tank is 10-100A / dm 2 , the electrodeposition time is 20-100s.
[0009] Furthermore, in the step 3, an acid copper plating solution is prepared and injected into two tanks respectively; Electroplating was performed on the composite peeling layer of the copper foil carrier, with the current density of the first slot being 20A / dm 2 , the electrodeposition time is 90s; After electroplating in the first tank, the copper foil carrier gradually passes through the squeeze roller, the water washing tank, and the squeeze roller to clean the front acid copper plating solution and enter the second tank for electroplating. The current density of the second tank is 18A / dm 2 , the electrodeposition time is 90s.
[0010] Furthermore, the pretreatment is a deoxidation treatment.
[0011] Furthermore, in step 2: the chromium-containing electroplating solution includes chromium trioxide and water, the concentration is 50-100 g / L, the plating temperature is 25-30°C, and the pH value is 0.5-3; the alloy-containing electroplating solution includes two or more of nickel salt, molybdenum salt, cobalt salt, and zinc salt, the total concentration of alloy salt is 30-200 g / L, and the plating temperature is 35-50°C.
[0012] Furthermore, the deposition process of the chromium stripping layer has a current density of 1-30A / dm 2 , the deposition time is 20-80s; the deposition process of the alloy peeling layer, the current density is 1-40A / dm 2 , the deposition time is 10-120s.
[0013] Furthermore, after the step three is completed, post-processing processes are also included: roughening treatment and curing treatment.
[0014] Furthermore, after the post-treatment process is completed, anti-oxidation treatment and / or silane coupling agent treatment is performed.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention deposits a chromium peeling layer and then an alloy peeling layer on the surface of a copper foil carrier to form a composite peeling layer, and then deposits a double-layer acidic ultra-thin copper foil layer. The thickness of the ultra-thin copper foil layer in the prepared ultra-thin carrier copper foil is about 2-5 μm, and the bonding strength between the ultra-thin copper foil and the carrier layer is equivalent. Complete peeling can be achieved in normal state and after lamination, and the ultra-thin copper foil layer has no pinholes and adhesion. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below in conjunction with the embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0017] Unless otherwise specified, the test materials and reagents used in the following embodiments can be obtained from commercial sources. If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the field or according to the product instructions.
[0018] Example 1 The specific preparation process is as follows.
[0019] Step 1: Deoxidize the metal foil carrier layer.
[0020] A 5 wt % sulfuric acid aqueous solution was used to clean the carrier copper foil used for support, with a thickness of 18 μm and a surface roughness of 0<Rz≤0.7 μm, to remove the oxide layer on the surface of the carrier copper foil.
[0021] Step 2: Deposit a composite release layer on the shiny side of the carrier copper foil.
[0022] A chromium-containing electroplating solution was prepared, the composition was 100 g / L chromium trioxide, the solvent was all water, the plating solution temperature was 25°C, and the pH value was 2; Prepare an alloy-containing electroplating solution with a composition of 30 g / L nickel sulfate and 50 g / L cobalt sulfate, a plating temperature of 45°C, and a pH value of 3; The chromium layer is electroplated on the smooth surface of the carrier copper foil treated in step 1, with a current density of 1A / dm 2 , the electrodeposition time is 10s; Continue to electroplate the alloy layer on the surface of the chromium layer with a current density of 5A / dm 2 , the electrodeposition time is 10s.
[0023] Step 3: Depositing ultra-thin copper foil on the composite peeling layer.
[0024] An acid copper plating solution was prepared with the composition of 80 g / L copper sulfate, 150 g / L sulfuric acid, 5 mg / L polyethylene glycol, and 0.2 mg / L methyl cellulose. The plating solution temperature was 50°C and was injected into two tanks respectively.
[0025] Electroplating was performed on the composite peeling layer of the copper foil carrier, with the current density of the first slot being 20A / dm 2 , the electrodeposition time is 90s; After electroplating in the first tank, the copper foil carrier gradually passes through the squeeze roller, the water washing tank, and the squeeze roller to clean the front acid copper plating solution and enter the second tank for electroplating. The current density of the second tank is 18A / dm 2 , the electrodeposition time is 90s.
[0026] The obtained peelable ultra-thin carrier copper foil comprises, from bottom to top, a copper foil carrier layer, a composite peeling layer and an ultra-thin copper foil layer.
[0027] Example 2 The preparation process is basically the same as that in Example 1, except that: When the strippable ultra-thin carrier copper foil is further applied to downstream, the prepared strippable ultra-thin carrier copper foil needs to be post-processed, including but not limited to roughening treatment, curing treatment, anti-oxidation treatment and / or silane coupling agent treatment.
[0028] Roughening treatment: Use high copper and low acid roughening solution. Copper sulfate 55g / L, sulfuric acid 100g / L, current density 15A / dm 2 , the electrodeposition time is 12s.
[0029] Curing treatment: Use low copper and high acid curing liquid. Copper sulfate 8g / L, sulfuric acid 110g / L, current density 5A / dm 2 , the electrodeposition time is 10s.
[0030] Anti-oxidation treatment and / or silane coupling agent treatment: Silane coupling agent treatment is used. Use acrylate type silane and spray to coat the treated surface.
[0031] The obtained peelable ultra-thin carrier copper foil comprises, from bottom to top, a metal foil carrier layer, a composite peeling layer, an ultra-thin copper foil layer, and a rough cured layer.
[0032] Example 3 The preparation process is basically the same as that in Example 1, except that: Step 3: Depositing ultra-thin copper foil on the composite peeling layer.
[0033] An acid copper plating solution was prepared with the composition of 80 g / L copper sulfate, 150 g / L sulfuric acid, 5 mg / L polyethylene glycol, and 0.2 mg / L methyl cellulose. The plating solution temperature was 50°C and was injected into two tanks respectively.
[0034] Electroplating was performed on the composite peeling layer of the copper foil carrier, with the current density of the first slot being 20A / dm 2 , the electrodeposition time is 75s; After electroplating in the first tank, the copper foil carrier gradually passes through the squeeze roller, the water washing tank, and the squeeze roller to clean the front acid copper plating solution and enter the second tank for electroplating. The current density of the second tank is 18A / dm 2 , the electrodeposition time is 75s.
[0035] Example 4 The preparation process is basically the same as that in Example 1, except that: Step 3: Depositing ultra-thin copper foil on the composite peeling layer.
[0036] An acid copper plating solution was prepared with the composition of 80 g / L copper sulfate, 150 g / L sulfuric acid, 5 mg / L polyethylene glycol, and 0.2 mg / L methyl cellulose. The plating solution temperature was 50°C and was injected into two tanks respectively.
[0037] Electroplating was performed on the composite peeling layer of the copper foil carrier, with the current density of the first slot being 25A / dm 2 , the electrodeposition time is 90s; After electroplating in the first tank, the copper foil carrier gradually passes through the squeeze roller, the water washing tank, and the squeeze roller to clean the front acid copper plating solution and enter the second tank for electroplating. The current density of the second tank is 15A / dm 2 , the electrodeposition time is 90s.
[0038] Example 5 The preparation process is basically the same as that in Example 1, except that: Step 3: Depositing ultra-thin copper foil on the composite peeling layer.
[0039] An acid copper plating solution was prepared with the composition of 80 g / L copper sulfate, 150 g / L sulfuric acid, 5 mg / L polyethylene glycol, and 0.2 mg / L methyl cellulose. The plating solution temperature was 50°C and was injected into two tanks respectively.
[0040] Electroplating was performed on the composite peeling layer of the copper foil carrier, with the current density of the first slot being 20A / dm 2 , the electrodeposition time is 75s; After electroplating in the first tank, the copper foil carrier gradually passes through the squeeze roller, the water washing tank, and the squeeze roller to clean the front acid copper plating solution and enter the second tank for electroplating. The current density of the second tank is 18A / dm 2 , the electrodeposition time is 75s.
[0041] Comparative Example 1 The preparation process is basically the same as that in Example 1, except that: Step 3: Depositing ultra-thin copper foil on the composite peeling layer.
[0042] Prepare an acid copper plating solution with the composition of 80 g / L copper sulfate, 150 g / L sulfuric acid, 5 mg / L polyethylene glycol, and 0.2 mg / L methyl cellulose. The plating solution temperature is 50°C; inject it only into the first tank.
[0043] Electroplating was performed on the composite peeling layer of the copper foil carrier, with the current density of the first slot being 30A / dm 2 , the electrodeposition time is 90s.
[0044] Comparative Example 2 The preparation process is basically the same as that in Example 1, except that: Step 3: Depositing ultra-thin copper foil on the composite peeling layer.
[0045] Prepare an alkaline copper plating solution, the composition of which is 30 g / L copper pyrophosphate, 230 g / L potassium pyrophosphate, and 5 g / L ammonia water, and inject it only into the first tank.
[0046] Electroplating was performed on the composite peeling layer of the copper foil carrier, with the current density of the first slot being 30A / dm 2 , the electrodeposition time is 90s.
[0047] Comparative Example 3 The preparation process is basically the same as that in Example 1, except that: Step 3: Depositing ultra-thin copper foil on the composite peeling layer.
[0048] Prepare an alkaline copper plating solution, the composition of which is 30 g / L copper pyrophosphate, 230 g / L potassium pyrophosphate, and 5 g / L ammonia water, and inject them into two tanks respectively.
[0049] Electroplating was performed on the composite peeling layer of the copper foil carrier, with the current density of the first slot being 20A / dm 2 , the electrodeposition time is 90s; After electroplating in the first tank, the copper foil carrier gradually passes through the squeeze roller, the water washing tank, and the squeeze roller to clean the front acid plating solution and enter the second tank for electroplating. The current density of the second tank is 18A / dm 2 , the electrodeposition time is 90s.
[0050] Comparative Example 4 The preparation process is basically the same as that in Example 1, except that: Step 3: Depositing ultra-thin copper foil on the composite peeling layer.
[0051] Prepare an alkaline copper plating solution, the composition of which is 30 g / L copper pyrophosphate, 230 g / L potassium pyrophosphate, 5 g / L ammonia water, and the plating temperature is 50° C. Pour it only into the first tank.
[0052] Prepare an acid copper plating solution with the composition of 80 g / L copper sulfate, 150 g / L sulfuric acid, 5 mg / L polyethylene glycol, and 0.2 mg / L methyl cellulose at a plating temperature of 50°C. Pour it only into the second tank.
[0053] Electroplating was performed on the composite peeling layer of the copper foil carrier, with the current density of the first slot being 20A / dm 2 , the electrodeposition time is 90s; After electroplating in the first tank, the copper foil carrier gradually passes through the squeeze roller, the water washing tank, and the squeeze roller to clean the front acid plating solution and enter the second tank for electroplating. The current density of the second tank is 18A / dm 2 , the electrodeposition time is 90s.
[0054] Performance Testing In order to illustrate that the copper foil obtained by the present invention is an ultra-thin copper foil, the basis weight of the carrier copper foil of each embodiment and comparative example was measured (using a 10*10 cm sample for testing), and the test results are shown in Table 1.
[0055] Table 1. Basis weight of each sample In order to show the peeling effect of the ultra-thin layer of the ultra-thin carrier copper foil on the preparation formulas of different embodiments and the sample obtained by the pressing plate is 150*50mm, the substrate of the pressing plate is FR-4 (epoxy glass cloth laminate), and the peeling force of the above-mentioned carrier copper foil sample after pressing is tested, and the test results are shown in Table 2.
[0056] Table 2. Peeling after pressing In order to more clearly show the effects of the preparation formulas of different embodiments on the peeling and pinhole conditions of the ultra-thin layer of the ultra-thin carrier copper foil, the carrier copper foils of the embodiments and comparative examples were peeled at room temperature and the ultra-thin layer was treated with acid to observe whether there were pinholes and acid penetration. The sample obtained was 1350*400mm, and the carrier copper foil samples were peeled at room temperature and treated with acid, respectively, and the test results are shown in Table 3.
[0057] Table 3. Peeling and pinhole conditions under normal conditions Performance test results: From Table 1 to Table 3, it can be seen that the thickness of the ultra-thin copper foil layer in the ultra-thin carrier copper foil prepared in Examples 1-4 is about 2-5 μm, and the bonding strength between the ultra-thin copper foil layer and the carrier layer is equivalent. Complete peeling can be achieved in normal state and after lamination, and the ultra-thin copper foil layer has no pinholes and adhesion.
[0058] It can be seen from Table 3 that Examples 1-4 can complete the peeling of the ultra-thin carrier with a full width of 1350 mm, and are uniform and pinhole-free. However, in step three of Comparative Example 1, a single acid is used, Comparative Example 2 uses a single base, and Comparative Example 3 uses a double layer of base, and the complete peeling of the ultra-thin carrier with a full width of 1350 mm cannot be completed, and pinholes or adhesion phenomena exist.
[0059] The "alkali + acid" electroplating process in comparative example 4 and the double-layer acid used in the present invention can both achieve complete peeling of the ultra-thin copper foil. However, the present invention only needs to configure a single plating solution, which requires lower costs, and there is no need to consider the cross-liquid and spraying of the front and rear acid and alkali plating solutions on the processing machine.
[0060] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A process for preparing a peelable ultra-thin carrier copper foil, comprising the following steps: Step 1: Pre-treat the metal foil carrier layer; the metal foil carrier is a copper foil carrier with a surface roughness of 0<Rz≤0.7μm Step 2: depositing a composite release layer on the glossy surface of the metal foil carrier; A chromium-containing electroplating solution and an alloy-containing electroplating solution are prepared respectively, and a chromium stripping layer is first deposited on the smooth surface of the pretreated metal foil carrier, and then an alloy stripping layer is deposited, and the two together serve as a composite stripping layer; Step 3: depositing an ultra-thin copper foil layer on the composite peeling layer; It is characterized in that The process for depositing the ultra-thin copper foil layer is secondary electroplating of an acid copper plating solution, wherein the acid copper plating solution comprises 70-90 g / L copper sulfate, 140-160 g / L sulfuric acid, 4-6 mg / L polyethylene glycol, and 0.1-0.3 mg / L methyl cellulose, and the temperature of the acid copper plating solution is 25-50°C.
2. The process for preparing a peelable ultra-thin carrier copper foil according to claim 1, characterized in that: The acid copper plating solution comprises 80 g / L copper sulfate, 150 g / L sulfuric acid, 5 mg / L polyethylene glycol and 0.2 mg / L methyl cellulose, and the temperature of the acid copper plating solution is 50° C.
3. A process for preparing a peelable ultra-thin carrier copper foil according to claim 1 or 2, characterized in that: In the step 3, an acid copper plating solution is prepared and injected into two tanks respectively; Electroplating is performed on the composite peeling layer of the copper foil carrier, and the current density of the first slot is 10-100A / dm 2 , the electrodeposition time is 20-100s; After electroplating in the first tank, the copper foil carrier gradually passes through the squeeze roller, the water washing tank, and the squeeze roller to clean the front acid copper plating solution and enter the second tank for electroplating. The current density of the second tank is 10-100A / dm 2 , the electrodeposition time is 20-100s.
4. The process for preparing a peelable ultra-thin carrier copper foil according to claim 3, characterized in that: In the step 3, an acid copper plating solution is prepared and injected into two tanks respectively; Electroplating was performed on the composite peeling layer of the copper foil carrier, with the current density of the first slot being 20A / dm 2 , the electrodeposition time is 90s; After electroplating in the first tank, the copper foil carrier gradually passes through the squeeze roller, the water washing tank, and the squeeze roller to clean the front acid copper plating solution and enter the second tank for electroplating. The current density of the second tank is 18A / dm 2 , the electrodeposition time is 90s.
5. The process for preparing a peelable ultra-thin carrier copper foil according to claim 1, characterized in that: The pretreatment is a deoxidation treatment.
6. The process for preparing a peelable ultra-thin carrier copper foil according to claim 1, characterized in that: In the step 2, the chromium-containing electroplating solution includes chromium trioxide and water, the concentration is 50-100 g / L, the plating temperature is 25-30°C, and the pH value is 0.5-3; the alloy-containing electroplating solution includes two or more of nickel salt, molybdenum salt, cobalt salt, and zinc salt, the total concentration of the alloy salt is 30-200 g / L, and the plating temperature is 35-50°C.
7. The process for preparing a peelable ultra-thin carrier copper foil according to claim 1, characterized in that: The deposition process of the chromium stripping layer has a current density of 1-30A / dm 2 , the deposition time is 20-80s; the deposition process of the alloy peeling layer, the current density is 1-40A / dm 2 , the deposition time is 10-120s.
8. The process for preparing a peelable ultra-thin carrier copper foil according to claim 1, characterized in that: After the step three is completed, post-processing processes are also included: roughening treatment and curing treatment.
9. The process for preparing a peelable ultra-thin carrier copper foil according to claim 8, characterized in that: After the post-treatment process is completed, anti-oxidation treatment and / or silane coupling agent treatment is performed.
10. A peelable ultra-thin carrier copper foil prepared according to the method according to any one of claims 1 to 9, characterized in that: From bottom to top, it includes a copper foil carrier layer, a composite peeling layer, and an ultra-thin copper foil layer, and the thickness of the ultra-thin copper foil layer is 2-5 μm.
Citation Information
Patent Citations
Preparation method of easy-to-peel ultrathin carrier copper foil and ultrathin carrier copper foil
CN118186525A